Valuation and willingness to pay for corn on the cob consumers in Mexico - Jauregui García, Carla Zulema; Espejel García, Anastacio; Hernández Montes, Arturo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The corn is a traditional food in Mexico that has been influenced by the current dynamics of the markets, causing the replacement of creole varieties by improved varieties and hybrids. Foods are characterized by a set of attributes that can be associated with a subjective evaluation, from which it is possible to approximate a utility function and determine elements for its evaluation. The objective of this work was to evaluate the Mexican consumer’s willingness to pay for various types of corn and to determine which of them have a higher valuation. The methodology was based on a contingent valuation study, with a total of 356 consumers selected by snowball sampling (95% reliability and 7% error) and answering a questionnaire designed in Google forms, addressing consumer sociodemographic information, characteristics corn and their willingness to pay. The willingness to pay extra for corn was significantly influenced when the consumer determined that it is important to know if the corn comes from Creole or modified seed and if it has any certification. Creole and imported corn obtained a greater willingness to pay, giving higher valuation to these products. In conclusion, the present work explores the economic valuation of corn, where significant factors can be used to induce an effect on consumers, particularly in the revaluation of creole corn.